Hematopoietic stem and progenitors cells gene editing: Beyond blood disorders - Buffa, Valentina; Alvarez Vargas, José Roberto; Galy, Anne; Spinozzi, Simone; Rocca, Céline J. (Frontiers in Genome Editing, 2023)
Lessons learned from decades-long practice in the transplantation of hematopoietic stem and progenitor cells (HSPCs) to treat severe inherited disorders or cancer, have set the stage for the current ex vivo gene therapies using autologous gene-modified HSPCs that have treated so far, hundreds of patients with monogenic disorders. With increased knowledge of HSPC biology, improved modalities for patient conditioning and with the emergence of new gene editing technologies, a new era of HSPC-based gene therapies is poised to emerge. Gene editing has the potential to restore physiological expression of a mutated gene, or to insert a functional gene in a precise locus with reduced off-target activity and toxicity. Advances in patient conditioning has reduced treatment toxicities and may improve the engraftment of gene-modified cells and specific progeny. Thanks to these improvements, new potential treatments of various blood- or immune disorders as well as other inherited diseases will continue to emerge. In the present review, the most recent advances in HSPC gene editing will be reported, with a focus on how this approach could be a promising solution to treat non-blood-related inherited disorders and the mechanisms behind the therapeutic actions discussed.